Les réseaux de personnages de science-fiction : échantillons de lectures intermédiaires - Yannick Rochat; Mathieu Triclot (ReS Futurae)
This paper introduces a way of studying science fiction works using mathematical methods grounded in graph theory. Our approach combines close and distant reading in order to describe the structural roles of characters, as they appear in the network built from their co-occurrences in the text. This study includes three main results. The first consists in the introduction of « middle reading », a method combining close and distant reading to analyze character systems in works of fiction. It relies on network visualization together with mathematical concepts like centrality or cluster detection. The second result consists in a typology of the works composing the corpus, based on the structure of their character networks. The third result is a reading proposal based on character qualification as scientist, technician or politician. This approach adds a dimension to these characters networks, thus allowing a richer interpretation of characters systems.